Femtosecond Soliton Erbium-Doped Fiber Laser With a Symmetrical GIMF–SIMF–GIMF Saturable Absorber - Qian-Chao Wu; Zhi-Ming Zou; Yong Yao; Jie Shi; Chong-Hao Wu; Yan-Fu Yang; Jia-Jun Tian; Ke Xu (IEEE Photonics Journal, 2019)
A femtosecond soliton erbium-doped fiber ring laser with the symmetrical saturable absorber (SA) of graded index multimode fiber-step index multimode fiber-graded index multimode fiber (GIMF-SIMF-GIMF) is proposed and proved. Based on the nonlinear multimode interference (NL-MMI) effect of SA, the fiber laser achieved femtosecond soliton mode-locking operation and repetition rate tuning. The duration of soliton was 364 fs at 1562.5 nm and repetition rate was tunable from 10.29 MHz to 763.36 MHz. In the structure of SA, a short step index multimode fiber (SIMF) was inserted between two graded index multimode fibers (GIMFs) to generate more high-order modes, adjust the self-focusing length, and improve operation stability of mode-locked fiber laser. The SA also has the advantages of immunity to the external environment variation, high damage threshold and inoxidizability, which make the laser operate stably for a long time.